2012
DOI: 10.1155/2012/640942
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Water on Three Different Light Cured Composite Restorative Materials Stored in Water: An In Vitro Study

Abstract: Objectives. The objective of this in vitro study was to investigate whether weight gain or loss in the three different composites occurs due to water absorption when they are stored in water.Methods. The composite restorative materials selected for this study included a microfine hybrid (Synergy) and two nanofilled composite restorative materials (Ceram X and Filtek Supreme Ultra). Twenty specimens of each material were fabricated of each composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
2
15
0
4
Order By: Relevance
“…This results meets findings in the literature, as there are reports that surface treatment is connected with restorations quality [10], therefore, rough surfaces have a negative effect, facilitating staining [28]. After the immersion periods conducted in this study, it was found that distilled water promoted its greater potential in color change in seven days, this can be explained by the fact that a large part of composite´s water absorption occurs in the first week [29].…”
Section: Discussionsupporting
confidence: 90%
“…This results meets findings in the literature, as there are reports that surface treatment is connected with restorations quality [10], therefore, rough surfaces have a negative effect, facilitating staining [28]. After the immersion periods conducted in this study, it was found that distilled water promoted its greater potential in color change in seven days, this can be explained by the fact that a large part of composite´s water absorption occurs in the first week [29].…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism for this is not fully understood, however it may be a result of differing interactions between lubricant components and their environment, over time. The greatest proportion of water uptake occurred in the first week, followed by a gradual decrease between the '1 week' and '12 week' assessments, similar to reported studies on water sorption [19,18,33]. It is clear that the instrument lubricants negatively affected/increased the water uptake of the composite specimens since their mean percentage weight change was significantly higher for the four experimental groups (with lubricant used), compared to the control group.…”
Section: 1: Diametral Tensile Strengthsupporting
confidence: 82%
“…Composite materials in the oral cavity undergo interaction with saliva [11][12][13][14][15], however none of the previous studies subjected their composite specimens to an immersion period to simulate such an environment. The inclusion of additional resin matrix from use of a lubricant may increase water uptake and result in increased hydrolytic degradation and have significant deleterious clinical consequences [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This results in loss of weight and can be measured as solubility or leaching. 12 A study done by Biradar et al 13 showed the maximum amount of water absorption in the first week, then a gradual decrease in the water absorption from the second to the 6th week, as compared with the 1st week. There was no statistically significant difference among the three tested composite resins.…”
Section: Discussionmentioning
confidence: 97%